HOW BRITISH AND AMERICAN ENGLISH SHAPE THE LEARNER'S THINKING, CONFIDENCE, AND SOCIAL BEHAVIOR - Toshtemirov Akbarjon Ravshan oʻgʻli (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The distinction between British and American English extends far beyond mere vocabulary and pronunciation differences, profoundly influencing how language  learners  develop  cognitive  patterns,  self-assurance,  and  interpersonal behaviors. This study examines the multifaceted impact of choosing between these two major English variants on learners' psychological and social development.  Through analysis of pedagogical research, sociolinguistic studies, and educational statistics, this paper  demonstrates  that  the  selection  of  either  British  or  American  English  as  a learning  model  significantly  affects  learners'  thought  processes,  communication confidence, and cultural identity formation. Research indicates that approximately 1.5 billion people worldwide are learning English, with the majority gravitating toward American English due to media exposure and globalization trends.  However,  learners  who  study  British  English  often  demonstrate  different linguistic  attitudes  and  social  perceptions.  This  investigation  explores  how phonological variations, lexical choices, grammatical structures, and cultural contexts embedded within each variant shape learners' cognitive frameworks, influence their self-perception in cross-cultural communication, and determine their social integration patterns.  The  findings  reveal  that  language  variant  selection  creates  distinct psychological imprints on learners, affecting their international mobility, professional opportunities, and intercultural competence.